REVIEWS (New blackfriars, 1985)
IMAGES OF BELIEF IN LITERATURE. Edited by David Jasper THE PROBABILITY OF GOD. By Hugh Montefiora THE GOD OF JESUS CHRIST by Walter Kaspar UNION WITH GOD, by Desmond Tillyer THE NATURE OF DOCTRINE: Religion and Theology in a Post-Liberal Age, by George A. Lindbeck GOSPEL LOVE, A NARRATIVE THEOLOGY by John Navone, SJ. Michael Glazier SPIRITUALITY AND JUSTICE, by Donal Dorr. Gill and Macmillan/Orbis